A modified hybrid model of heat exchanger based on fouling effect - Lei Zhao; Wenjian Cai; Xudong Ding (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
Hybrid model is a simple and accurate model for stable heat transfer process. Its theoretical basis shows that it is inappropriate to be applied to system with severe coefficient drifting. However, coefficient drifting is normal phenomenon in power and chemical industrial due to fouling. In this paper, a modified hybrid model of heat exchanger is proposed. The derivation of system is based on heat transfer balance and fouling principle of the heat exchanger. Considering fouling effect, a comprehensive model is derived. The catalog results with experiment data show that the proposed model can predict accurately the real-time performance of heat exchanger with error less than 3%. This model can be used in heat exchanger with high fouling risk for operational optimization, performance assessment and device maintaining.